Recess as a practical strategy to implement the Whole School, Whole Community, Whole Child model in schools. (March 2021) - McLoughlin, Gabriella M; Massey, William V; Lane, Hannah G; Calvert, Hannah G; Turner, Lindsey; Hager, Erin R
Objectives: Schools can provide an optimal environment for promoting children's health behaviours. The Whole School, Whole Community, Whole Child (WSCC) model addresses 10 aspects of the school environment that can be used to promote student health behaviours and academic outcomes: namely, Health Education; Nutrition Environment and Services; Employee Wellness; Social and Emotional School Climate; Physical Environment; Health Services; Counselling, Psychological and Social Services; Community Involvement; Family Engagement; and Physical Education and Physical Activity. Design: Guidelines for practical use of the WSCC model for school professionals are limited, impeding potential impact on school health promotion. Accordingly, in this article, we seek to demonstrate an application of the WSCC model to a specific school-based practice: recess. Setting: School recess. Results: An overview of literature and evidence-informed practices details how recess can facilitate WSCC adoption and initial implementation. Areas requiring further empirical research prior to making additional recommendations are also discussed. Conclusion: Strategies to enhance learning and health are described, attempting to bridge the gap between research and practice in school settings using the WSCC model.